Little pretty things a novel - Rader-Day, Lori 1973- (Amherst, NY Seventh Street Books, an imprint of Prometheus Books, 2015)
"OLD RIVALRIES NEVER DIE. BUT SOME RIVALS DO. Juliet Townsend is used to losing. Back in high school, she lost every track team race to her best friend, Madeleine Bell. Ten years later, she's still running behind, stuck in a dead-end job cleaning rooms at the Mid-Night Inn, a one-star motel that attracts only the cheap or the desperate. But what life won't provide, Juliet takes. Then one night, Maddy checks in. Well-dressed, flashing a huge diamond ring, and as beautiful as ever, Maddy has it all. By the next morning, though, Juliet is no longer jealous of Maddy--she's the chief suspect in her murder. To protect herself, Juliet investigates the circumstances of her friend's death. But what she learns about Maddy's life might cost Juliet everything she didn't realize she had"--
1
Keywords: FICTION / Mystery & Detective / General; FICTION / Mystery & Detective / Women Sleuths; Hotel cleaning personnel -- Fiction; Murder -- Investigation -- Fiction; Mystery fiction